Robot-assisted laparoscopic retroperitoneal lymph node dissection in testicular cancer using a single-position supine approach: A case report and literature review - Lei Zhou; Kun Yao; Chao Li; Wei Xiong; Weibin Hou; Bingzhi Wang; Long Xu; Long Wang (Current Urology)
Abstract. This case study demonstrates a single-position supine approach for robotic retroperitoneal lymph node dissection (R-RPLDN) for the treatment of nonseminomatous germ cell tumors and residual masses after chemotherapy. We performed a bilateral R-RPLDN in a 33-year-old man with nonseminomatous germ cell tumors and residual postchemotherapy masses. For this approach, the patient was placed in a steep Trendelenburg position, and a 5-port transperitoneal technique was used, with the robot docked so that the arms were oriented cephalad. This approach allowed simultaneous access to both sides of the retroperitoneum, thereby eliminating the need for bilateral lymphadenectomy and patient repositioning. Bilateral R-RPLDN was performed using a single-position supine approach. This versatile approach offers a less invasive, more efficient, and safer solution for removing residual postchemotherapy testicular cancer masses.